PERAN ORANG TUA DAN GURU DALAM MENANAMKAN NILAI AGAMA MORAL DAN PENCEGAHAN PERUNDUNGAN PADA ANAK USIA DINI - Rosida Rosida; Muhammad Turhan Yani; Achmad Sya’dullah (CV. ADIBA AISHA AMIRA, 2024)
The aim of this research is to understand the roles of parents and teachers in instilling moral and religious values and preventing bullying in early childhood. This study employs the Library Research method. Data collection techniques include gathering various journals, articles, research findings, books, and other records to address the research questions. Data analysis involves data reduction followed by data display, and finally, summarizing the research findings. The specific subject of this study pertains to the roles of parents and teachers in instilling moral and religious values and preventing bullying in early childhood. Based on the results of the Library Research, it is evident that the roles of parents and teachers are crucial in the character development of early childhood. Children at a young age exhibit unique characteristics that are often challenging for their environment to accept. When their desires are not met, they may resort to bullying behavior, which is often unnoticed by parents due to a lack of attention given to the child and insufficient interaction, leading to deviant behavior in children.